Deciphering the role of SlWRKY36 and SlWRKY51 in salt stress tolerance via modulating ion homeostasis and proline biosynthesis - Iqra Mehboob; Sofia Baig; Maria Siddique; Xiaoliang Shan; Ayesha Baig; Mohammad Maroof Shah; Irum Shahzadi; Hongwei Zhao; Shamyla Nawazish; Samina Khalid (Current Plant Biology, 2024)
Soil salinity caused by NaCl is a major challenge to agricultural crops worldwide. For this, two WRKY transcription factors were evaluated for their role in salt stress tolerance in tomato plants (Solanum lycopersicum; Sl). SlWRKY36 and SlWRKY51 provided novel insight into the regulatory mechanism in tomato against salt stress via virus-induced gene silencing (VIGS). Salt stress significantly reduced chlorophyll-a, an abundant form of chlorophyll content to 6.0 and 5.1 mg/g and proline content to 0.06 mg/g and 0.09 mg/g respectively in SlWRKY36 and SlWRKY51 silenced tomato plants. This shows that salt stress affected proline content that act as osmo-protectant and damaged photosynthetic pigments in silenced SlWRKY36 and SlWRKY51 tomato plants. Similarly, the concentrations of Na+/ K+ ratio also showed a significantly higher trend 14 days after salt stress with 5.5 mg/g and 8.9 mg/g concentration at 200 mM for SlWRKY36 and SlWRKY51 showing silencing promotes Na+/K+ ion ratio under salt stress. Also, salt stress responsive genes such as salt overly sensitive SOS1 and Na+/H+ exchanger NHX1 displayed lower transcript level in silenced plants at 200 mM salt stress showing their negative regulation by SlWRKY36 and SlWRKY51 gene silencing. Collectively, these findings suggest for the first time the role of SlWRKY36 and SlWRKY51 as positive regulators of salt stress tolerance by managing ion homeostasis, proline content and photosynthetic machinery via transcriptional reprogramming. Overall, SlWRKY36 and SlWRKY51 were explored as potential candidates for engineering salt tolerance in tomato crop plants.